2018
DOI: 10.1007/s13311-017-0586-z
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Ischemic Stroke Models in Nonhuman Primates

Abstract: To bridge the gap between rodent and human studies, the Stroke Therapy Academic Industry Roundtable committee suggests that nonhuman primates (NHPs) be used for preclinical, translational stroke studies. Owing to the fact that vast majority of ischemic strokes are caused by transient or permanent occlusion of a cerebral blood vessel eventually leading to brain infarction, ischemia induced by endovascular methods closely mimics thromboembolic or thrombotic cerebrovascular occlusion in patients. This review will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…But, it was difficult to make a biopsy to explore mechanisms in patients. NHP models have great advantages in translational studies, such as a bigger brain volume and higher percentage of WM, and possible pathological analysis [34]. In this study, we observed a tissue rescue from day 1 to day 30 based on MRI images.…”
Section: Discussionsupporting
confidence: 55%
“…But, it was difficult to make a biopsy to explore mechanisms in patients. NHP models have great advantages in translational studies, such as a bigger brain volume and higher percentage of WM, and possible pathological analysis [34]. In this study, we observed a tissue rescue from day 1 to day 30 based on MRI images.…”
Section: Discussionsupporting
confidence: 55%
“…Genetically, the genomic sequence similarity of non-human primates and humans is as high as 92%. 21 Anatomically, non-human primates have developed a complete Willis artery circle and distributions of the internal carotid and vertebral arteries as those in humans, 2224 not to mention the ability of non-human primates to perform some of the sophisticated tasks, ensuring that neurological function could be assessed. 25 As such, as a transition to a potential clinical trial, a rhesus monkey ischemic model is used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Endotracheal intubation may efficiently address the issue of respiratory failure and should be considered in future experiments. Prostration was a sign of cerebral compression caused by oedema, which can be fatal as reported in other non-human primate models of stroke [29]- [31]. In our study, we tackled this complication with high dose of dexamethasone, which improved symptoms drastically and prevented oedema-related mortality.…”
Section: Discussionmentioning
confidence: 74%